SEGURANÇA DO PACIENTE PEDIÁTRICO NA ADMINISTRAÇÃO DE HEMOCOMPONENTES - Mayane Magalhães Santos (2022)
Introduction: The therapeutic use of blood components is a notorious healthcare practice in hospitalization situations and the lack of standardization of its use in children can result in unsafe situations. Objective: to analyze pediatric patient safety in blood components administration. Method: This was a documental, retrospective, quantitative study, developed in a tertiary care hospital in central-western Brazil. The collection occurred between April and July 2021, period in which 234 transfusions were analyzed, performed in 90 patients from zero to twelve years of age, admitted between July and December 2020. For data collection, we used: an instrument based on criteria applied for structuring hemotherapy services; and good practice guidelines for the use of blood components. Data collection was based on the analysis of eligible patients' medical records and information from the blood components requisition form, medical prescription, and transfusion agency and nursing reports. For the analysis, descriptive and inferential statistics were used, considering a 5% significance level. All ethical principles were followed. Results: Transfusions occurred (71.1%) in infants, (21.1%) in infants and (7.8%) were in middle childhood. Blood Transfusion predominated in critical sectors (86.3%), with clinical order indication (87.2%) and the prescription of packed red blood cells (75.3%). No transfusion reactions, adverse events or incidents were reported in the period; however, adverse events (n=05) and incidents (n=137) in transfusions were identified in the nursing report and were statistically associated to inadequate volume prescribed and infused, and request and administration time (p<0.001). Conclusion: The administration of blood components presented nonconformities, especially regarding the volume and time indicated, which results in risk situations for the pediatric patient.